First multi-year retrospective study on Vibrio parahaemolyticus and Vibrio vulnificus prevalence in Ruditapes philippinarum harvested in Sacca di Goro, Italy - Patrizia Serratore (Italian Journal of Food Safety, 2016)
The present work describes a retrospective study aiming to verify a possible correlation between the environmental conditions (temperature, salinity and dissolved oxygen), the abundance of Vibrio spp., and the prevalence of V. parahaemolyticus and V. vulnificus in the Manila clam R. philippinarum harvested in Sacca di Goro, Emilia-Romagna Region, Northern Italy. On the whole, 104 samples, collected in the period 2007-2015 and submitted to microbiological analyses (isolation and genotyping), have been reconsidered for Vibrio spp. load, V. parahaemolyticus prevalence (total, gene marker toxRP; potentially pathogenic, gene markers tdh and/or trh) and V. vulnificus prevalence (total, gene markers vvhA and hsp) together with environmental data obtained from the monitoring activity of the Emilia-Romagna Regional Agency for the Prevention, the Environment and the Energy. Environmental data have been processed to calculate the median of each, assessing the seasonal range of seawater temperature (warmer months: April-October, T°C >16.45°C; cooler months November-March, T°C 27 psu), and dissolved oxygen (< or >8.2 mg/L). Total V. vulnificus, total and potentially pathogenic V. parahaemolyticus were present respectively in the 11.5, 29.8 and 6.7% of the samples. The Vibrio spp. load (mean value of 4.69±0.65 log10 colony forming unit g-1) and the prevalence of potentially pathogenic V. parahaemolyticus, were not significantly correlated to the environmental conditions (P>0.05), whereas the prevalence of both total V. vulnificus and total V. parahaemolyticus was significantly higher in the warmer period (P<0.05), without correlation with salinity and dissolved oxygen values (P>0.05).